Pericardial Tamponade following Asymptomatic SARS-CoV-2 Infection: A Diagnostic Journey - Christian Birner; Matthias Gasche; Rainer Voisard; Christian Neumann (Case Reports in Cardiology)
Background. Pericardial tamponade is a known life-threatening condition rarely reported in COVID-19 but has not been reported following asymptomatic SARS-CoV-2 infection. Its pathomechanism is still elusive. Case Summary. We report the case of a 66-year-old man with progressive shortness of breath and leg swelling due to new-onset heart failure and pericardial tamponade following asymptomatic SARS-CoV-2 infection. Ultrasound-guided placement of a pericardial drainage led to significant improvement of symptoms and revealed an exudative effusion. Throughout the diagnostic process, we were confronted with a systemic inflammatory syndrome suspicion of an induced autoimmune condition. After steroid pulse therapy and oral anticoagulation for subclavian vein thrombosis, the patient was discharged and followed in our outpatient clinic. Discussion. Patients with asymptomatic SARS-CoV-2 infection are at risk for developing life-threatening complications. Induced autoimmune conditions could be a potential explanation for late-onset pericardial tamponade in this population. A multimodal imaging approach is crucial in the diagnosis and characterization of cardiac inflammation. An interdisciplinary approach is essential. Awareness of uncommon cardiac complications following a SARS-CoV-2 infection is crucial for the initial assessment and the appropriate treatment of these patients.